Non-Decriminalization of Political Offenses in Indonesia: A Study on Article 154 of the Criminal Code (KUHP) - Parmono, Budi; Hidayati, Rahmatul; Ahnaf, Muhammad Qatrunnada (Budapest International Research and Critics University, 2025)
Article 154 of the Indonesian Criminal Code (Kitab Undang-undang Hukum Pidana; KUHP) is classified as a political offense because it is directed against the state, aims at public harm (public wrong), and involves non-violent expression of enmity or contempt (oral, written, or visual). The Dutch Government, however, viewed Article 154 KUHP as undemocratic and contrary to free expression and opinion, arguing it was only justifiable in colonial Indonesia for their interests. This created a divergence between the legislative interests of a colonized nation and a democratic one regarding 'expression' or 'opinion'. The Netherlands has equivalent provisions in Articles 137a to 137e of their Criminal Code, focusing on public insult against authorities or specific groups. While the Dutch code formulates these as formal insult offenses, Indonesia’s Article 154 KUHP is broader, covering both formal and material insult. Notably, Articles 137a and 137b of the Dutch Criminal Code were revoked in 1978 for conflicting with Dutch freedom of expression, while Article 154 KUHP remains enforced in Indonesia because its elements are considered identical to Political Offenses.